(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research lies in using an educational approach according to the Osborne model in learning some skills in volleyball, laying the correct scientific foundations when using the Osborne model, and thus this research contributes seriously to studying one of the field problems in learning some skills in volleyball. The research aims to identify: Preparing an educational curriculum according to the Osbron model that is compatible with the capabilities of the research sample. Identify the effect of an educational approach according to the Osbron model on learning some volleyball skills. An experimental approach was used and the research sample was chosen from the Sulaikh Sports Club players, who are (12) learners, ages (16-17) years old. The results showed that the educational units showed significant differences in learning some skills in volleyball between the experimental and control groups in the post-test and in favor of the experimental group in tests among the learners. The recommendation was made on the necessity of using the Osbron model in learning for its effectiveness in facilitating the delivery of information to learners.